ANALYSIS OF HUMAN RESOURCE DEVELOPMENT INDEX: 6 CITIES OF CENTRAL JAVA PROVINCE - Wahyu Tri Nur Ahmad Firdaus; Didit Welly Udjianto (Yayasan Education and Social Center, 2023)
This study aims to determine the extent to which factors such as poverty, the average number of years spent in school, the district minimum wage, and per capita expenditure all have an impact on the human development index (HDI) in six cities located in Central Java in the years 2010-202. The method used is associative with quantitative from the publication of the Central Java Province Statistics Agency (BPS).Â The data used is panel data consisting of cross-section data in the form of city and time series data for 2010-2021. The results showed that the minimum wage had a positive and significant effect on HDI, poverty had a positive and insignificant effect on HDI, average years of schooling had a significant positive effect on HDI, and adjusted per capita expenditure had a positive and significant effect on HDI. The coefficient of determination in this study's independent variables influences 99.08% of HDI. At the same time, the other 1.92% is influenced by other variables